Implementation of Wayang Media in Learning The History of Islamic Culture in MI - Asmawati Asmawati (Social Studies Conference Proceedings, 2022)
Learning Islamic Cultural History (SKI) is one of the essential subjects in Islamic studies at Madrasah Ibtidaiyah. SKI subjects contain Islamic history materials that motivate students to know, recognize, and live Islamic history, which will directly or indirectly shape the attitudes and character of students. Historical SKI materials should be conveyed to students in the right way and media so that the learning objectives can be achieved. In schools, there is still a lot of SKI learning, which is explained by the lecture and question and answer method, making SKI learning to tend to be boring for students. The media used did not vary. On the other hand, educators can use many media to explain SKI material well, interestingly, and fun for students, one of which is wayang media. Wayang media can be used to assist educators in conveying material that involves important figures in history. This study aims to implement wayang media in SKI learning. The research used is quantitative with a quantitative descriptive approach. The results of this study describe the implementation of wayang media that meets valid criteria, with validation results by material experts reaching 98.60% and media experts validating 97.05%. The response of students and educators subject to product trials was outstanding.